Capnocytophaga canimorsus-associated sepsis presenting as acute abdomen: do we need to think outside the box?. Issue 3 (14th March 2019) - Ahmad, Soban; Yousaf, Amman; Inayat, Faisal; Anjum, Shahzad
Abstract : Capnocytophaga canimorsus is a commensal bacterium commonly found in the oral cavity of dogs and cats. Although this organism rarely causes infection, prompt diagnosis is crucial for survival of these patients. Several unusual clinical presentations of this infection have been reported in the published medical literature. The present report represents the first case of C. canimorsus -related sepsis presenting with symptoms of acute abdomen in a patient with no known history of immunodeficiency. Prompt aggressive care and appropriate antibiotic therapy resulted in a successful clinical outcome with no long-term morbidity. This paper illustrates that clinicians should include this infectious aetiology among the differentials of patients presenting with acute abdomen, regardless of their immune status. Additionally, this paper outlines our current understanding of the epidemiology of and risk factors for C. canimorsus -associated sepsis, the pathophysiology of this disorder, and currently available approaches to diagnosis and management.